Pola Manajemen Keuangan dan Dampak Kenaikan Biaya Produksi terhadap Ketahanan Keuangan Pada Pelaku UMKM (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to find out whether MSME actors have implemented the right financial resilience so they are ready to face unexpected increases in production costs. The method used in this study uses a qualitative method, namely a method that aims to find out the phenomenon of what is experienced by the research subject and describe it in the form of words. The results of this study are that MSME actors have not implemented financial security properly.